Efektivitas Konsumsi Mixed Jus Mentimun dan Belimbing terhadap Penurunan Tekanan Darah pada Klien Hipertensi - leniwita, Hasian; Adventus, Adventus; Mertajaya, I Made (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of giving a mixture of star fruit and cucumber juice on reducing blood pressure in the elderly at Panti Sasana Tresna Werdha (PSTW) Ria, Jakarta development. The method used is a one-group pre-test and post-test design approach. Population and sampling used simple random sampling techniques with a total of 30 respondents. The research results show the results of univariate and bivariate analysis with the t-test p.value = 0.000. This shows that the administration of a mixture of star fruit and cucumber juice has a significant effect on reducing blood pressure. In conclusion, there is an effect of giving a mixture of star fruit and cucumber juice in reducing blood pressure in hypertension sufferers. Keywords: Hypertension, Mixed Juice,Blood Pressure